Fablehaven. [Book three], Grip of the shadow plague - Mull, Brandon, 1974-; Dorman, Brandon ([Salt Lake City, Utah] : Shadow Mountain, 2008)
At Kendra and Seth's grandparent's estate, which is a sanctuary for magical creatures, Seth discovers that somehow a plague has been released that transforms beings of light into creatures of darkness. Where to turn for help? Meanwhile Kendra and the Knights of the Dawn journey to a distant preserve to try and retrieve another hidden artifact.
Keywords: Magic -- Juvenile fiction; Grandparents -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Good and evil -- Juvenile fiction